Londonstani - Malkani, Gautam, 1976- (New York Penguin Books, 2007)
Gautam Malkani tells of a Britain that has never before been explored in the novel: a country of young Asian and white boys (desis and goras) trying to work out a place for themselves in the shadow of the divergent cultures of their parent's generation.
Include Glossary
Keywords: South Asians -- England--London -- Young men